Strategies to Attain Faculty Work-Life Balance - Joan Owens; Carol Kottwitz; Jane Tiedt; Jeffery Ramirez (The Ohio State University Libraries, 2018)
Background: Achieving work-life balance can be a challenge for academic faculty members. The multifaceted demands and expectations of the role can affect faculty satisfaction and the ability to attain work-life balance. The ever-changing trends in higher education, including technology and online education modalities provide additional factors that can inhibit faculty satisfaction and work-life balance. Aims: This paper explores barriers to achieving work-life balance such as cognitive dissonance, emotional dissonance and burnout. Understanding barriers is essential to developing strategies to promote work-life balance. Methods: An integrated review of the literature on life balance of academic faculty in all disciplines using multiple online databases. Conclusion: Strategies, organized around mentoring and self-care, include promoting physical health, connecting socially, and practicing mindfulness as a cognitive approach can help counteract work-place stressors and help in achieving work-life balance.